Disordered redox metabolism of brain cells in rats exposed to low doses of ionizing radiation or uhf electromagnetic radiation - Burlaka, A.P.; Druzhyna, M.O.; Vovk, A.V.; Lukin, S.M. (Experimental Oncology, 2016)
Aim: To investigate the changes of redox-state of mammalian brain cells as the critical factor of initiation and formation of radiation damage of biological structures in setting of continuous exposure to low doses of ionizing radiation or fractionated ultra high frequency electromagnetic radiation (UHF EMR) at non-thermal levels. Materials and Methods: The influence of low-intensity ionizing radiation was studied on outbred female rats kept for 1.5 years in the Chernobyl accident zone. The effects of total EMR in the UHF band of non-thermal spectrum were investigated on Wistar rats. The rate of formation of superoxide radicals and the rate of NO synthesis in mitochondria were determined by the EPR. Results: After exposure to ionizing or UHF radiation, the levels of ubisemiquinone in brain tissue of rats decreased by 3 and 1.8 times, respectively. The content of NO-FeS-protein complexes in both groups increased significantly (р < 0.05). In the conditions of ionizing or EMR the rates of superoxide radical generation in electron-transport chain of brain cell mitochondria increased by 1.5- and 2-fold, respectively (р < 0.05). In brain tissue of rats kept in the Chernobyl zone, significant increase of NO content was registered; similar effect was observed in rats treated with UHFR (р < 0.05). Conclusions: The detected changes in the electron transport chain of mitochondria of brain cells upon low-intensity irradiation or UHF EMR cause the metabolic reprogramming of cell mitochondria that increases the rate of superoxide radical generation and nitric oxide, which may initiate the development of neurodegenerative diseases and cancer. This article is part of a Special Issue entitled “The Chornobyl Nuclear Accident: Thirty Years After”.